Super-hygroscopic polymer and preparation method thereof
Through the synergistic effects of hydroxypropyl cellulose, konjac glucomannan, graphene oxide and lithium chloride, a new super hygroscopic polymer was developed, which solved the problems of reduced water absorption capacity and high desorption energy consumption in existing hygroscopic materials under low humidity conditions, and achieved efficient water absorption and rapid water release effects, which were suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411830638.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-11
AI Technical Summary
The existing moisture-absorbing materials have reduced water absorption capacity under low humidity conditions, high desorption energy consumption, and complex preparation process and high cost, making it difficult to achieve large-scale production.
Using the synergistic action of hydroxypropyl cellulose, konjac glucomannan, graphene oxide and lithium chloride, a new super hygroscopic polymer was developed by adjusting the component ratio of the material and the preparation process.
The material exhibits efficient water absorption under low humidity conditions and achieves rapid moisture release through temperature control. It has a simple preparation process, stable circulation performance and low cost. It is suitable for air moisture collection, air purification and industrial dehumidification.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hygroscopic materials, in particular to a super hygroscopic polymer and a preparation method thereof. Background Art
[0002] About two-thirds of the world's population is facing varying degrees of water shortage, especially in arid areas, where the challenge of obtaining fresh water resources is becoming increasingly severe. Although desalination and water purification technologies are constantly developing, these technologies usually require a lot of energy and complex infrastructure. Moisture in the atmosphere has attracted more and more attention as a sustainable source of fresh water, especially in water-scarce areas. However, existing air moisture collection technologies, such as fog capture and dew condensation, usually rely on high relative humidity and are difficult to operate effectively under low humidity (≤30% RH) conditions.
[0003] In low humidity environments, the water absorption capacity of commonly used hygroscopic materials such as zeolite and silica gel is significantly reduced, and a large amount of energy is consumed in the process of water release. In addition, although hygroscopic salts such as lithium chloride have excellent water absorption capacity, they are prone to crystallization and aggregation during the hydration process, resulting in a slow adsorption rate and reduced recycling performance. In order to overcome these problems, researchers have also developed adsorbent metal organic frameworks (MOFs) and covalent organic frameworks (COFs) materials. However, the synthesis process of these materials is complex, the production environment requirements are strict, the cost is high, and it is difficult to achieve large-scale production, which limits the widespread promotion of their practical applications.
[0004] In order to solve the above problems, there is an urgent need for a hygroscopic material that can efficiently absorb water under low humidity conditions and has low desorption energy consumption, while also having a simple preparation process, stable cycle performance and low cost. This provides an important research direction for the development of new super hygroscopic polymer materials. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention aims to provide a super absorbent polymer and a preparation method thereof.
[0006] The above object of the present invention is achieved through the following technical solutions:
[0007] A super absorbent polymer is prepared by comprising the following components in parts by weight:
[0008]
[0009] The concentration of the graphene oxide aqueous suspension is 8-12 mg / mL.
[0010] Furthermore, the weight average molar mass of the hydroxypropyl cellulose is 60,000 to 90,000.
[0011] Furthermore, the hydroxypropyl content of the hydroxypropyl cellulose is 20-30%.
[0012] Furthermore, the viscosity of the hydroxypropyl cellulose is greater than 500 mPa·s.
[0013] Furthermore, the content of glucomannan in the konjac glucomannan is greater than 90%.
[0014] Furthermore, the ash content of the hydroxypropyl cellulose and konjac glucomannan is less than 0.5%.
[0015] Furthermore, the mass ratio of the hydroxypropyl cellulose to the konjac glucomannan is 1:0.8-4.
[0016] The present invention provides a novel super hygroscopic polymer, which achieves remarkable technical effects in water absorption and desorption performance through the synergistic effect of hydroxypropyl cellulose, konjac glucomannan, graphene oxide and lithium chloride. The material has high water absorption capacity and can achieve rapid water release through temperature control. It is suitable for air moisture collection, air purification and industrial dehumidification, and has potential wide application in arid areas.
[0017] First of all, konjac glucomannan (KGM), as a natural high-molecular polysaccharide, has a strong water absorption capacity and can absorb water tens of times more than its own weight. Combining konjac glucomannan with hydroxypropyl cellulose (HPC) further improves the water absorption performance of the material. Konjac glucomannan and hydroxypropyl cellulose work together to form a porous structure, which significantly increases the specific surface area of the material and effectively improves the water absorption rate and amount. In addition, the glucomannan content in konjac glucomannan is greater than 90%, ensuring its high purity and high efficiency in the material; at the same time, the viscosity of hydroxypropyl cellulose is greater than 500mPa·s, and the weight-average molar mass is controlled between 60,000 and 90,000, so that it can form a stable structure when combined with konjac glucomannan, thereby significantly improving the water absorption capacity.
[0018] As one of the important components of the present invention, lithium chloride further enhances the hygroscopicity of the material. Lithium chloride is a highly hygroscopic substance with extremely strong hydrophilicity, which can significantly increase the material's adsorption capacity for water molecules. When combined with hydroxypropyl cellulose and konjac glucomannan, lithium chloride can quickly absorb moisture from the air and transfer it to the porous structure inside the polymer through osmosis, promoting the distribution of moisture throughout the material. This rapid moisture absorption property combined with the porous structure of HPC and KGM enables the material to absorb large amounts of moisture more effectively and increase the moisture absorption rate.
[0019] In addition, lithium chloride also plays a key role in the desorption process. Because it is highly soluble in water, lithium chloride can help the adsorbed water to be quickly released from the material. This property works synergistically with the thermal responsiveness of hydroxypropyl cellulose. When the temperature rises above 45°C, HPC changes from hydrophilic to hydrophobic, and water molecules are repelled and accelerated by the action of lithium chloride. Therefore, lithium chloride not only improves the water absorption capacity of the material, but also significantly enhances its desorption performance, especially in scenarios where rapid release of water is required.
[0020] As a two-dimensional nanomaterial, the sheet structure of graphene oxide provides mechanical support for the polymer, avoiding possible structural collapse during water absorption. In addition, the oxygen functional groups on its surface form a synergistic effect with hydroxypropyl cellulose and konjac glucomannan, improving the overall moisture absorption capacity. During the desorption process, the hydrophobicity of graphene oxide further accelerates the release of water, especially in high temperature environments, it exhibits excellent thermal conductivity and thermal stability, thereby achieving a fast and effective desorption effect.
[0021] Hydroxypropyl cellulose is a thermoresponsive polymer whose hydrophilicity and hydrophobicity change significantly with temperature. At lower temperatures (such as below 45°C), hydroxypropyl cellulose exhibits hydrophilicity and can effectively absorb water. When the temperature rises above 45°C, the hydrogen bonds in HPC dissociate and the hydrophilic hydroxyl groups (–OH) are replaced by the hydrophobic methyl groups (–CH 3 ) is replaced, causing it to become hydrophobic and promote the rapid release of water. This thermal responsiveness greatly improves the desorption performance of the material, enabling it to maintain good performance stability during moisture absorption-desorption. At the same time, the porous structure of konjac glucomannan enhances this performance, by providing a larger specific surface area and more moisture storage space, allowing the material to release moisture more quickly and effectively at higher temperatures. Secondly, graphene oxide has a certain hydrophobicity. The addition of graphene oxide can further enhance the stability of the material structure and reduce the thermal conductivity of the material, thereby further enhancing the water release rate of the material at high temperatures.
[0022] By rationally controlling the mass ratio of hydroxypropyl cellulose and konjac glucomannan (1:0.8-4), the porosity and specific surface area of the material can be effectively adjusted, thereby affecting the water absorption rate and water storage capacity of the material. Within this mass ratio range, HPC and KGM can form a porous structure with a large specific surface area, thereby significantly improving the water absorption rate and water absorption amount. The pore structure inside the material not only increases the water absorption capacity of the material, but also provides an effective way for the subsequent release of water.
[0023] The hydroxypropyl cellulose, konjac glucomannan, graphene oxide and lithium chloride in the present invention not only improve the water absorption and desorption performance of the material through synergistic effect, but also ensure the overall structural stability of the material. The porosity of konjac glucomannan provides mechanical support for the material to prevent its structural collapse during water absorption. At the same time, the high purity and low ash content (<0.5%) of konjac glucomannan effectively avoid the interference of impurities on the performance of the material, ensuring the stability of the material in long-term use. Both the hydroxypropyl cellulose and konjac glucomannan in the material have a low ash content, which helps to improve the purity and functional performance of the material.
[0024] The material is environmentally friendly, with a wide range of raw materials and low cost. In particular, konjac glucomannan, as a natural biomaterial, is renewable and biodegradable, which is in line with the current trend of green environmental protection. At the same time, the preparation process of the material is relatively simple, which can be completed by uniform mixing and appropriate heat treatment, suitable for large-scale production, and has a good industrialization prospect. Since the material exhibits excellent hygroscopic properties in low temperature environments, it does not require high-energy consumption equipment for temperature control, thereby reducing the cost of use and maintenance.
[0025] In addition, the material has a wide range of application prospects. In the field of air moisture collection, especially in arid or semi-arid areas, the material can effectively alleviate the problem of water shortage by absorbing moisture in the air. In terms of industrial dehumidification, the material can quickly absorb moisture in the air and help keep the production environment dry. It is suitable for dehumidification needs in workshops, warehouses and other environments. At the same time, the material's hygroscopic properties also make it perform well in air purifiers, further improving air quality by absorbing moisture and impurities in the air.
[0026] The super hygroscopic polymer material provided by the present invention can further optimize the water absorption rate, water absorption and desorption performance of the material by adjusting the hydroxypropyl content (20-30%) of hydroxypropyl cellulose and the proportion of konjac glucomannan. The higher the hydroxypropyl content in HPC, the stronger its hydrophilicity and the higher its water absorption capacity, but at the same time, the hydrophobic performance will be reduced when the temperature rises. By flexibly adjusting the combination ratio of HPC, KGM and lithium chloride, the material performance can be customized to meet the hygroscopic requirements under different environments.
[0027] In general, the present invention provides a novel super hygroscopic polymer through the synergistic effect of hydroxypropyl cellulose, konjac glucomannan and lithium chloride, which has excellent water absorption performance and controllable desorption characteristics, and can be widely used in multiple fields such as air moisture collection, dehumidification and air purification. The addition of lithium chloride not only further improves the moisture absorption and desorption capacity of the material, but also provides stronger support for the overall performance of the material. This material not only has obvious advantages in performance, but also has a simple and environmentally friendly preparation process and the potential for large-scale production, providing a new solution to solve the problem of water shortage in arid areas.
[0028] A method for preparing a super hygroscopic polymer comprises the following steps:
[0029] S1: adding lithium chloride powder to the hydroxypropyl cellulose solution according to the proportion, and stirring until the lithium chloride is completely dissolved to form solution A;
[0030] S2: Add konjac glucomannan powder to solution A in proportion. After konjac glucomannan is completely dissolved in solution A, add 10 mg / mL of graphene oxide aqueous suspension until it is stirred evenly. Pour the mixed liquid into a mold at room temperature and let it stand until the bubbles on the surface have dissipated and the liquid forms a gel;
[0031] S3: Place the gel together with the mold into a -5 to -25°C refrigerator and freeze for more than 24 hours until the gel shrinks to form a clear solid state, and then perform vacuum freeze-drying to obtain a super hygroscopic polymer.
[0032] Furthermore, in the step S3, the gel and the mold are placed in a refrigerator and the freezing temperature is controlled to be -10 to -15°C, and the freezing time is controlled to be 36 to 48 hours.
[0033] Furthermore, the temperature of the vacuum freeze-drying in step S3 is controlled at -80°C, and the vacuum freeze-drying time is 12 to 24 hours.
[0034] The method for preparing a super hygroscopic polymer of the present invention realizes the efficient water absorption and desorption performance of the material through reasonable process steps and in combination with the characteristics of the material. First, in step S1, lithium chloride powder is added to the hydroxypropyl cellulose solution and completely dissolved, ensuring that lithium chloride is evenly distributed in the system, thereby effectively enhancing the hygroscopic capacity of the material. As a strong hygroscopic agent, lithium chloride synergizes with the thermal responsiveness of hydroxypropyl cellulose, not only improving the material's ability to absorb water, but also accelerating the desorption process of water.
[0035] In step S2, konjac glucomannan powder and graphene oxide are added to a mixed solution of lithium chloride and hydroxypropyl cellulose to form a stable gel. In this process, the high viscosity and water absorption capacity of konjac glucomannan further enhance the overall hygroscopic properties of the material, while the porous structure formed by it and hydroxypropyl cellulose increases the specific surface area, promoting the rapid absorption and accumulation of water. The formation of the gel state lays the foundation for the subsequent structural shaping of the material, and ensures the uniformity of the internal structure of the material by standing and defoaming, avoiding bubbles from affecting its performance. The oxygen functional groups on the surface of graphene oxide form a synergistic effect with hydroxypropyl cellulose and konjac glucomannan, which not only improves the overall hygroscopic capacity, but also optimizes the thermal conductivity of the material.
[0036] In step S3, the gel is frozen and shrunk and solidified by a low-temperature environment. This freezing process not only ensures the mechanical stability of the material, but also further optimizes the porous structure of the material through freeze-drying. By controlling the freezing temperature and time, fine and uniform pores are formed inside the material. This structure is conducive to improving water absorption and water storage capacity. The vacuum freeze-drying process ensures the complete removal of water while retaining the porous structure, effectively improving the moisture absorption rate and moisture absorption of the material. In the overall process, reasonable temperature and time control enable the super hygroscopic polymer to have good mechanical strength and structural stability while maintaining efficient hygroscopic properties.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] First, the introduction of lithium chloride enhances the material's hygroscopic capacity. As a strong hygroscopic agent, lithium chloride can quickly absorb moisture from the environment and transfer the moisture evenly to the interior of the material through its combination with hydroxypropyl cellulose. This primary hygroscopic property provides the material with a basic and efficient water absorption capacity. Then, the thermal responsiveness of hydroxypropyl cellulose further improves the material's water absorption and desorption performance. Under low temperature conditions, the hydrophilicity of hydroxypropyl cellulose allows the material to quickly absorb moisture; when the temperature rises, its hydrophobicity allows the moisture to be effectively discharged. This thermal responsiveness conversion ensures that the material can not only absorb a large amount of water, but also quickly release water when needed, thereby increasing the desorption rate. In addition, the introduction of graphene oxide provides a significant structural enhancement for the material. Its two-dimensional sheet structure not only improves the mechanical strength and stability of the material, but also further optimizes the hygroscopic and desorption performance through the synergistic effect of surface oxygen functional groups and other components. The hydrophobicity of graphene oxide accelerates the release of water at high temperatures, and its low thermal conductivity also helps to improve the thermal efficiency during the desorption process at high temperatures. Finally, the porous structure formed by konjac glucomannan and freeze-drying process ensures the overall performance stability of the material. This porous structure not only expands the specific surface area of the material, enhances the water absorption rate and water storage capacity, but also ensures the structural stability of the material in the moisture absorption and desorption cycle, maintaining high efficiency while having good mechanical strength. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with embodiments.
[0040] Example 1
[0041] A super absorbent polymer disclosed in this embodiment is prepared by including the following components in parts by weight:
[0042]
[0043] The weight average molar mass of hydroxypropyl cellulose is 60,000.
[0044] The hydroxypropyl content of hydroxypropyl cellulose is 20%.
[0045] The viscosity of hydroxypropyl cellulose is greater than 500mPa·s.
[0046] The content of glucomannan in konjac glucomannan is 93%.
[0047] The ash content in hydroxypropyl cellulose and konjac glucomannan is less than 0.5%.
[0048] The concentration of the graphene oxide aqueous suspension is 8 mg / mL.
[0049] The method for preparing a super absorbent polymer comprises the following steps:
[0050] S1: mixing hydroxypropyl cellulose and water in proportion to obtain a hydroxypropyl cellulose solution, adding lithium chloride powder to the hydroxypropyl cellulose solution in proportion, and stirring until the lithium chloride is completely dissolved to form a solution A;
[0051] S2: Add konjac glucomannan powder to solution A in proportion. After konjac glucomannan is completely dissolved in solution A, add graphene oxide aqueous suspension and stir evenly. Pour the mixed liquid into a mold at room temperature and let it stand for 1 hour until the bubbles on the surface have dissipated and the liquid forms a gel.
[0052] S3: Place the gel together with the mold in a -12°C refrigerator and freeze for 48 hours until the gel shrinks to form a clear solid state, and then perform vacuum freeze-drying. The vacuum freeze-drying temperature is controlled at -80°C and the vacuum freeze-drying time is 12 hours to obtain a super hygroscopic polymer.
[0053] Example 2
[0054] A super absorbent polymer disclosed in this embodiment is prepared by including the following components in parts by weight:
[0055]
[0056] The weight average molar mass of hydroxypropyl cellulose is 90,000.
[0057] The hydroxypropyl content of hydroxypropyl cellulose is 30%.
[0058] The viscosity of hydroxypropyl cellulose is greater than 500mPa·s.
[0059] The content of glucomannan in konjac glucomannan is 93%.
[0060] The ash content in hydroxypropyl cellulose and konjac glucomannan is less than 0.5%.
[0061] The concentration of the graphene oxide aqueous suspension is 12 mg / mL.
[0062] The method for preparing a super absorbent polymer comprises the following steps:
[0063] S1: mixing hydroxypropyl cellulose and water in proportion to obtain a hydroxypropyl cellulose solution, adding lithium chloride powder to the hydroxypropyl cellulose solution in proportion, and stirring until the lithium chloride is completely dissolved to form a solution A;
[0064] S2: Add konjac glucomannan powder to solution A in proportion. After konjac glucomannan is completely dissolved in solution A, add graphene oxide aqueous suspension and stir evenly. Pour the mixed liquid into a mold at room temperature and let it stand for 1 hour until the bubbles on the surface have dissipated and the liquid forms a gel.
[0065] S3: Place the gel together with the mold in a -12°C refrigerator and freeze for 48 hours until the gel shrinks to form a clear solid state, and then perform vacuum freeze-drying. The vacuum freeze-drying temperature is controlled at -80°C and the vacuum freeze-drying time is 12 hours to obtain a super hygroscopic polymer.
[0066] Example 3
[0067] A super absorbent polymer disclosed in this embodiment is prepared by including the following components in parts by weight:
[0068]
[0069] The weight average molar mass of hydroxypropyl cellulose is 80,000.
[0070] The hydroxypropyl content of hydroxypropyl cellulose is 26%.
[0071] The viscosity of hydroxypropyl cellulose is greater than 500mPa·s.
[0072] The content of glucomannan in konjac glucomannan is 94%.
[0073] The ash content in hydroxypropyl cellulose and konjac glucomannan is less than 0.5%.
[0074] The concentration of the graphene oxide aqueous suspension is 10 mg / mL.
[0075] The method for preparing a super absorbent polymer comprises the following steps:
[0076] S1: mixing hydroxypropyl cellulose and water in proportion to obtain a hydroxypropyl cellulose solution, adding lithium chloride powder to the hydroxypropyl cellulose solution in proportion, and stirring until the lithium chloride is completely dissolved to form a solution A;
[0077] S2: Add konjac glucomannan powder to solution A in proportion. After konjac glucomannan is completely dissolved in solution A, add graphene oxide aqueous suspension and stir evenly. Pour the mixed liquid into a mold at room temperature and let it stand for 1 hour until the bubbles on the surface have dissipated and the liquid forms a gel.
[0078] S3: Place the gel together with the mold in a -12°C refrigerator and freeze for 48 hours until the gel shrinks to form a clear solid state, and then perform vacuum freeze-drying. The vacuum freeze-drying temperature is controlled at -80°C and the vacuum freeze-drying time is 12 hours to obtain a super hygroscopic polymer.
[0079] Example 4
[0080] A super absorbent polymer disclosed in this embodiment is prepared by including the following components in parts by weight:
[0081]
[0082]
[0083] The weight average molar mass of hydroxypropyl cellulose is 80,000.
[0084] The hydroxypropyl content of hydroxypropyl cellulose is 26%.
[0085] The viscosity of hydroxypropyl cellulose is greater than 500mPa·s.
[0086] The content of glucomannan in konjac glucomannan is 94%.
[0087] The ash content in hydroxypropyl cellulose and konjac glucomannan is less than 0.5%.
[0088] The concentration of the graphene oxide aqueous suspension is 10 mg / mL.
[0089] The method for preparing a super absorbent polymer comprises the following steps:
[0090] S1: mixing hydroxypropyl cellulose and water in proportion to obtain a hydroxypropyl cellulose solution, adding lithium chloride powder to the hydroxypropyl cellulose solution in proportion, and stirring until the lithium chloride is completely dissolved to form a solution A;
[0091] S2: Add konjac glucomannan powder to solution A in proportion. After konjac glucomannan is completely dissolved in solution A, add graphene oxide aqueous suspension and stir evenly. Pour the mixed liquid into a mold at room temperature and let it stand for 1 hour until the bubbles on the surface have dissipated and the liquid forms a gel.
[0092] S3: Place the gel together with the mold in a -12°C refrigerator and freeze for 48 hours until the gel shrinks to form a clear solid state, and then perform vacuum freeze-drying. The vacuum freeze-drying temperature is controlled at -80°C and the vacuum freeze-drying time is 12 hours to obtain a super hygroscopic polymer.
[0093] Example 5
[0094] A super absorbent polymer disclosed in this embodiment is prepared by including the following components in parts by weight:
[0095]
[0096] The weight average molar mass of hydroxypropyl cellulose is 80,000.
[0097] The hydroxypropyl content of hydroxypropyl cellulose is 26%.
[0098] The viscosity of hydroxypropyl cellulose is greater than 500mPa·s.
[0099] The content of glucomannan in konjac glucomannan is 94%.
[0100] The ash content in hydroxypropyl cellulose and konjac glucomannan is less than 0.5%.
[0101] The concentration of the graphene oxide aqueous suspension is 10 mg / mL.
[0102] The method for preparing a super absorbent polymer comprises the following steps:
[0103] S1: mixing hydroxypropyl cellulose and water in proportion to obtain a hydroxypropyl cellulose solution, adding lithium chloride powder to the hydroxypropyl cellulose solution in proportion, and stirring until the lithium chloride is completely dissolved to form a solution A;
[0104] S2: Add konjac glucomannan powder to solution A in proportion. After konjac glucomannan is completely dissolved in solution A, add graphene oxide aqueous suspension and stir evenly. Pour the mixed liquid into a mold at room temperature and let it stand for 1 hour until the bubbles on the surface have dissipated and the liquid forms a gel.
[0105] S3: Place the gel together with the mold in a -12°C refrigerator and freeze for 48 hours until the gel shrinks to form a clear solid state, and then perform vacuum freeze-drying. The vacuum freeze-drying temperature is controlled at -80°C and the vacuum freeze-drying time is 12 hours to obtain a super hygroscopic polymer.
[0106] Example 6
[0107] A super absorbent polymer disclosed in this embodiment is prepared by including the following components in parts by weight:
[0108]
[0109] The weight average molar mass of hydroxypropyl cellulose is 80,000.
[0110] The hydroxypropyl content of hydroxypropyl cellulose is 26%.
[0111] The viscosity of hydroxypropyl cellulose is greater than 500mPa·s.
[0112] The content of glucomannan in konjac glucomannan is 94%.
[0113] The ash content in hydroxypropyl cellulose and konjac glucomannan is less than 0.5%.
[0114] The concentration of the graphene oxide aqueous suspension is 10 mg / mL.
[0115] The method for preparing a super absorbent polymer comprises the following steps:
[0116] S1: mixing hydroxypropyl cellulose and water in proportion to obtain a hydroxypropyl cellulose solution, adding lithium chloride powder to the hydroxypropyl cellulose solution in proportion, and stirring until the lithium chloride is completely dissolved to form a solution A;
[0117] S2: Add konjac glucomannan powder to solution A in proportion. After konjac glucomannan is completely dissolved in solution A, add graphene oxide aqueous suspension and stir evenly. Pour the mixed liquid into a mold at room temperature and let it stand for 1 hour until the bubbles on the surface have dissipated and the liquid forms a gel.
[0118] S3: Place the gel together with the mold into a -20°C refrigerator and freeze for 48 hours until the gel shrinks to form a clear solid state, and then perform vacuum freeze-drying. The vacuum freeze-drying temperature is controlled at -80°C and the vacuum freeze-drying time is 12 hours to obtain a super hygroscopic polymer.
[0119] Example 7
[0120] A super absorbent polymer disclosed in this embodiment is prepared by including the following components in parts by weight:
[0121]
[0122] The weight average molar mass of hydroxypropyl cellulose is 80,000.
[0123] The hydroxypropyl content of hydroxypropyl cellulose is 26%.
[0124] The viscosity of hydroxypropyl cellulose is greater than 500mPa·s.
[0125] The content of glucomannan in konjac glucomannan is 94%.
[0126] The ash content in hydroxypropyl cellulose and konjac glucomannan is less than 0.5%.
[0127] The concentration of the graphene oxide aqueous suspension is 10 mg / mL.
[0128] The method for preparing a super absorbent polymer comprises the following steps:
[0129] S1: mixing hydroxypropyl cellulose and water in proportion to obtain a hydroxypropyl cellulose solution, adding lithium chloride powder to the hydroxypropyl cellulose solution in proportion, and stirring until the lithium chloride is completely dissolved to form a solution A;
[0130] S2: Add konjac glucomannan powder to solution A in proportion. After konjac glucomannan is completely dissolved in solution A, add graphene oxide aqueous suspension and stir evenly. Pour the mixed liquid into a mold at room temperature and let it stand for 1 hour until the bubbles on the surface have dissipated and the liquid forms a gel.
[0131] S3: Place the gel together with the mold in a -8°C refrigerator and freeze for 48 hours until the gel shrinks to form a clear solid state, and then perform vacuum freeze-drying. The vacuum freeze-drying temperature is controlled at -80°C and the vacuum freeze-drying time is 12 hours to obtain a super hygroscopic polymer.
[0132] Comparative Example 1
[0133] The difference between Comparative Example 1 and Example 1 is that the super absorbent polymer does not contain lithium chloride. The preparation method comprises the following steps:
[0134] S1: mixing hydroxypropyl cellulose and water in proportion to obtain a hydroxypropyl cellulose solution, and stirring until the lithium chloride is completely dissolved to form a solution A;
[0135] S2: adding konjac glucomannan powder to solution A according to a certain proportion, and after konjac glucomannan is completely dissolved in solution A, pouring the mixed liquid into a mold at room temperature, and letting it stand for 1 hour until all bubbles on the surface have dissipated and the liquid forms a gel;
[0136] S3: Place the gel together with the mold in a -8°C refrigerator and freeze for 48 hours until the gel shrinks to form a clear solid state, and then perform vacuum freeze-drying. The vacuum freeze-drying temperature is controlled at -80°C and the vacuum freeze-drying time is 12 hours to obtain a super hygroscopic polymer.
[0137] Comparative Example 2
[0138] The difference between Comparative Example 2 and Example 1 is that the super absorbent polymer does not contain graphene oxide suspension. The preparation method comprises the following steps:
[0139] S1: mixing hydroxypropyl cellulose and water in proportion to obtain a hydroxypropyl cellulose solution, adding lithium chloride powder to the hydroxypropyl cellulose solution in proportion, and stirring until the lithium chloride is completely dissolved to form a solution A;
[0140] S2: adding konjac glucomannan powder to solution A according to a certain proportion, and after konjac glucomannan is completely dissolved in solution A, pouring the mixed liquid into a mold at room temperature, and letting it stand for 1 hour until all bubbles on the surface have dissipated and the liquid forms a gel;
[0141] S3: Place the gel together with the mold in a -8°C refrigerator and freeze for 48 hours until the gel shrinks to form a clear solid state, and then perform vacuum freeze-drying. The vacuum freeze-drying temperature is controlled at -80°C and the vacuum freeze-drying time is 12 hours to obtain a super hygroscopic polymer.
[0142] Detection Methods
[0143] The materials of Examples 1 to 7 and Comparative Examples 1 and 2 were placed in a constant temperature and humidity chamber for water absorption and release tests. The following Tables 1 to 9 show the results of the water absorption test. The unit of saturated water absorption is the percentage of the material's own weight. For example, 100% means that the maximum water absorption of 1g of material is also 1g.
[0144] Table 1 Example 1 Water absorption test results
[0145] Environmental relative humidity (%) Saturated water absorption (%) Saturation time (minutes) 15 60 100 30 90 70 60 150 55
[0146] Table 2 Example 2 Water absorption test results
[0147] Environmental relative humidity (%) Saturated water absorption (%) Saturation time (minutes) 15 50 110 30 80 80 60 140 60
[0148] Table 3 Example 3 Water absorption test results
[0149]
[0150]
[0151] Table 4 Example 4 Water absorption test results
[0152] Environmental relative humidity (%) Saturated water absorption (%) Saturation time (minutes) 15 60 110 30 80 90 60 130 60
[0153] Table 5 Example 5 Water absorption test results
[0154] Environmental relative humidity (%) Saturated water absorption (%) Saturation time (minutes) 15 65 110 30 85 80 60 140 65
[0155] Table 6 Example 6 Water absorption test results
[0156] Environmental relative humidity (%) Saturated water absorption (%) Saturation time (minutes) 15 70 100 30 90 65 60 130 55
[0157] Table 7 Example 7 Water absorption test results
[0158] Environmental relative humidity (%) Saturated water absorption (%) Saturation time (minutes) 15 65 100 30 95 70 60 120 60
[0159] Table 8 Comparative Example 1 Water absorption test results
[0160] Environmental relative humidity (%) Saturated water absorption (%) Saturation time (minutes) 15 60 170 30 85 120 60 110 100
[0161] Table 9 Comparative Example 2 Water Absorption Experiment Results
[0162]
[0163]
[0164] At the same time, the samples of the materials of Examples 1 to 7 and Comparative Example 1 were subjected to a water release test at a temperature of 60° C. after being saturated with water at an ambient relative humidity of 60%. The test results are shown in Table 10 below.
[0165] Table 10
[0166] Example 80% of absorbed water release time (min) Example 1 15 Example 2 19 Example 3 18 Example 4 16 Example 5 17 Example 6 17 Example 7 16 Comparative Example 1 28 Comparative Example 2 33
[0167] The above test results show that the super absorbent polymer material formed by hydroxypropyl cellulose, konjac glucomannan and lithium chloride has better moisture absorption and desorption effects, and has better effects in terms of water absorption, water absorption efficiency and water release efficiency.
[0168] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A super hygroscopic polymer, characterized in that The preparation comprises the following components in parts by weight: The concentration of the graphene oxide aqueous suspension is 8-12 mg / mL.
2. A super absorbent polymer according to claim 1, characterized in that: The weight average molar mass of the hydroxypropyl cellulose is 60,000-90,000.
3. A super absorbent polymer according to claim 1, characterized in that: The hydroxypropyl content of the hydroxypropyl cellulose is 20-30%.
4. A super absorbent polymer according to claim 1, characterized in that: The viscosity of the hydroxypropyl cellulose is greater than 500 mPa·s.
5. A super absorbent polymer according to claim 1, characterized in that: The content of glucomannan in the konjac glucomannan is greater than 90%.
6. A super absorbent polymer according to claim 1, characterized in that: The ash content of the hydroxypropyl cellulose and konjac glucomannan is less than 0.5%.
7. A super absorbent polymer according to claim 1, characterized in that: The mass ratio of the hydroxypropyl cellulose to the konjac glucomannan is 1:0.8-4.
8. A method for preparing a super absorbent polymer according to claims 1 to 9, characterized in that: The steps include: S1: adding lithium chloride powder to the hydroxypropyl cellulose solution according to the proportion, and stirring until the lithium chloride is completely dissolved to form solution A; S2: Add konjac glucomannan powder to solution A in proportion. After konjac glucomannan is completely dissolved in solution A, add 10 mg / mL of graphene oxide aqueous suspension until it is stirred evenly. Pour the mixed liquid into a mold at room temperature and let it stand until the bubbles on the surface have dissipated and the liquid forms a gel; S3: The gel and the mold are placed in a -5 to -25°C refrigerator and frozen for more than 24 hours, and then freeze-dried in a vacuum to obtain a super hygroscopic polymer.
9. The method for preparing a super absorbent polymer according to claim 8, characterized in that: In the step S3, the gel and the mold are placed in a refrigerator and the freezing temperature is controlled to be -10 to -15°C, and the freezing time is controlled to be 36 to 48 hours.
10. The method for preparing a super absorbent polymer according to claim 8, characterized in that: The temperature of the vacuum freeze-drying in step S3 is controlled at -80°C, and the vacuum freeze-drying time is 12 to 24 hours.